An empirical survey of topologies, evolution, and current developments in multilevel inverters - G. Ezhilarasan; K. Mohanraj; Pradeep Vishnuram; Mohit Bajaj; Vojtech Blazek; Lukas Prokop; Stanislav Misak (Alexandria Engineering Journal, 2023)
The majority of high-power, high-voltage, and high-power medium-voltage electronic applications now need multi-level inverters (MLIs), which are becoming a required technology. MLIs may provide a wide range of output levels designed to meet the diverse requirements of high voltage/power applications. In addition to the increased output levels, MLI can mitigate the total harmonic distortion (THD) and perform the function of voltage stress (dv/dt) reduction across the power switches. The overwhelming development of new MLI topologies on existing ones multiplies its potential to stimulate more output levels with fewer components. Moreover, the most recent MLI topologies use symmetrical dc sources to produce comparable output levels with fewer semiconductor switches, decreasing capital costs and improving system reliability. In essence, asymmetrical DC source values can be obtained from various unconventional energy sources, including solar, wind, etc. As a result, the various topologies were proposed with an asymmetrical structure for balancing the unequal DC voltage sources and converting them into AC voltages with balanced conditions. This comprehensive review will provide an in-depth analysis of various MLI setups based on switch count, switching methods, symmetric structures, asymmetric topologies, and hybrid configurations.